Fatigue analysis of a railway bridge based on fracture mechanics and local modelling of riveted connections. (December 2018) - Marques, Fernando; Correia, José A.F.O.; de Jesus, Abílio M.P.; Cunha, Álvaro; Caetano, Elsa; Fernandes, Augusto A.
Abstract: In the context of fatigue evaluation of riveted railway bridges, cross-girder to main beam connections are frequently critical details. Secondary effects, such as out-of-plane bending and dynamic amplifications due to the proximity to loading paths which in the case of old bridges were not taken into account in the original design, may lead to severe increase of fatigue damage. The fatigue assessment of old riveted railway bridges has been addressed in the last years by developing local models of critical riveted joints that are linked to global models. This local-global modelling approach aims at evaluating local secondary stresses. Former fatigue probabilistic analyses of riveted joints have been focused on resistance variability rather than on loading/stresses (actions) variability. In this paper a probabilistic procedure to include the variability of loading in the fatigue analysis of complex riveted joints of railway bridges is proposed assuming loading as a random variable. Local finite element models were developed and later coupled with the global model in order to obtain the real stresses associated to real trains crossing the bridge. To reduce computational time, the results obtained from these local models were inputted in a Linear Fracture Mechanics model, supported by Paris fatigue crack propagation law. Monte Carlo simulation technique was applied to calculate the fatigue reliability of an old riveted railway bridge, considering traffic records from previous studies on the bridge. Highlights: Proposed probabilistic procedure to include loading variability in fatigue analysis of riveted joints of railway bridges. Local FEM coupled with global model in order to obtain the real stresses associated to real trains crossing the bridge. Results from the local FEM inputted in a Linear Fracture Mechanics model, supported by Paris fatigue crack propagation law. The shape functions from local finite element model for extreme trains were calculated. Monte Carlo simulation technique implemented for fatigue reliability of an old riveted railway bridge.